2013
DOI: 10.1590/s1981-67232013005000011
|View full text |Cite
|
Sign up to set email alerts
|

Biofilmes nanocompósitos obtidos de isolado proteico de corvina (Micropogonias furnieri) e Montmorilonita: avaliação das propriedades físicas, mecânicas e de barreira

Abstract: O objetivo deste trabalho foi avaliar as propriedades de biofilmes nanocompósitos de isolado proteico de corvina (Micropogonias furnieri) com argila organofílica. Inicialmente, foi obtido isolado proteico de corvina (IPC) utilizando-se o processo de mudança de pH. O IPC foi obtido a partir de subprodutos da industrialização de corvina. Para o desenvolvimento dos filmes, foi executado um planejamento experimental de Box e Behnken, com três níveis de IPC (2; 3,5; 5 g.100 g-1 de solução), argila montmorilonita MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…The thickness was determined as the arithmetic average of five random measurements of the area of the film, it was found that with an increase in solids, thickness increased too, same behavior found by Brandelero et al [12] who determined thicknesses of starch films in the same way and obtained a variation in thickness from 0.11 mm to 0.33 mm. On the other hand, Cortez-Vega et al [13] also determined the film thickness of croaker protein isolate by the mean of 10 thickness measurements. Therefore, the value of the average thickness (0.2 mm) was maintained for the planning, according to the amount of solution placed in the plate (15.5 g), since these values showed better tensile strength and elongation to break characteristics from preliminary tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thickness was determined as the arithmetic average of five random measurements of the area of the film, it was found that with an increase in solids, thickness increased too, same behavior found by Brandelero et al [12] who determined thicknesses of starch films in the same way and obtained a variation in thickness from 0.11 mm to 0.33 mm. On the other hand, Cortez-Vega et al [13] also determined the film thickness of croaker protein isolate by the mean of 10 thickness measurements. Therefore, the value of the average thickness (0.2 mm) was maintained for the planning, according to the amount of solution placed in the plate (15.5 g), since these values showed better tensile strength and elongation to break characteristics from preliminary tests.…”
Section: Discussionmentioning
confidence: 99%
“…According to the process conditions, the tensile strength of the films of chicken protein isolate with montmorillonite ranged from 6.7 to 9.1MPa and elongation to break of 26-66%. On the other hand, Zavareze et al [15] found tensile strength ranging from 4.0 to 5.7MPa and elongation to break of 102-193% in myofibrillar fish protein films, in croaker protein isolate films with the addition of montmorillonite found TS from 7.2 to 10.7MPa and elongation to break from 39.6 to 45.8% [13] .It can be seen then that the films obtained in this work showed reasonable resistance compared to other films derived from meat protein isolates, possibly due to the addition of montmorillonite, obtaining values close to those of Cortez-Vega et al [13] who also used nanoclay. As for the elongation, variability greater than that of other authors was obtained.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultados diferentes foram encontrados por Fakhouri et al, 13 que trabalharam com filmes de gelatina, adicionado de ácido láurico, variando entre 31,83 a 57,38 MPa, onde se notou que a resistência diminuía com a concentração de lipídios. CortezVega et al, 18 também encontraram resultados diferentes em seu estudo com filmes biopoliméricos obtidos de isolado proteico de corvina e argila montmorilonita, variando entre 7,2 e 7,3 MPa.…”
Section: Tabelaunclassified
“…Estes resíduos (aparas de filetagem e peles) podem ser transformados em novos produtos pela indústria aumentando a renda e criando novos empregos. As aparas e peles contêm alto teor de proteínas, miofibrilares e colágeno, que possuem habilidade para formar redes, plasticidade e elasticidade, boa barreira ao oxigênio podendo ser utilizados na elaboração de filmes biodegradáveis (Cortez-Vega et al, 2013).…”
Section: Introductionunclassified